Evaluating Axial and Radial Compression-Induced Stress and Deformation in Watermelon Fruits - Chibuzo Ndubuisi Okoye; Christian Ebele Chukwunyelu; John Chikaelo Okeke; Augustine Uzodinma Madumere; Chukwunonso Nnamdi chidiogo; Sunday Chimezie Anyaora (Journal Majelis Paspama, 2025)
Understanding the mechanical behavior of biological materials such as watermelon fruits under compressive loading is essential for improving postharvest handling, packaging, and transport systems. This study utilized experimental and finite element methods to evaluate stress and deformation in watermelon fruits under axial and radial compression. Fresh, defect-free watermelons were measured and tested using a universal testing machine until failure. Mechanical properties such as modulus of elasticity, Poisson’s ratio, and bulk modulus were computed. Simulation in Autodesk® Inventor® used these parameters to model stress distribution, safety factors, and deformation under a 95 N load. The elliptical mesh model included 3529 nodes and 2264 elements. Each test was repeated thrice for accuracy. The result revealed that Axial loading showed higher modulus of elasticity (2.68 MPa), Poisson’s ratio (0.43), and bulk modulus (0.94 MPa) compared to radial loading (2.41 MPa, 0.33, and 0.91 MPa respectively). Fracture load remained consistent (95 N). Von Mises stress under axial loading peaked at (1.238 MPa) versus radial (0.02701 MPa). Safety factor under axial loading was critically low (0.14), unlike radial (5.71). Orthogonal stress components (XX, YY, ZZ) revealed greater stress concentration under axial loading (e.g., −1.02 MPa to 0.059 MPa in XX). Finite element modeling used (3529) nodes and (2264) elements for analysis. These findings reveal that axial compression presents a higher risk of structural failure in watermelons, highlighting the importance of orientation during handling and mechanical design for fruit protection.